Association of Angiotensin-Converting Enzyme Insertion/Deletion Polymorphism with Recurrent Pregnancy Loss: a Meta-Analysis of 26 Case-Control Studies - Aslbahar, Fereshteh; Neamatzadeh, Hossein; Tabatabaiee, Razieh Sadat; Karimi-Zarchi, Mojgan; Javaheri, Atiyeh; Mazaheri, Mahta; Foroughi, Elnaz; Nasiri, Rezvan (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective Previous studies investigating the association between angiotensin-converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism and recurrent pregnancy loss (RPL) risk has provided inconsistent results. The aim of our study was to assess the association between the ACE I/D polymorphism and risk of RPL.Methods All studies published up to January 30, 2018 on the association of ACE I/D polymorphism with RPL were identified by searching the PubMed, Web of Knowledge, and Google scholar databases.Results A total of 26 case-control studies with 3,140 RPL cases and 3,370 controls were included in the meta-analysis. Overall, there was a significant association between ACE I/D polymorphism and RPL risk under the allele model (I versus D: odds ratio [OR] = 0.538, 95% confidence interval [CI] = 0.451–0.643, p ≤ 0.001), the homozygote model (II versus DD: OR = 0.766, 95% CI = 0.598–0.981, p = 0.035) and the recessive model (II versus ID + DD: OR = 0.809, 95% CI = 0.658–0.994, p = 0.044). Subgroup analysis by ethnicity showed that there was a significant association between ACE I/D polymorphism and increased risk of RPL in Caucasian and West-Asian populations, but not in East-Asians. When stratified by number of recurrent miscarriages (RMs), a significant association between ACE I/D polymorphism and increased risk of RPL was detected in the group of studies with ≥ 2 RMs, but not in studies with ≥ 3 RMs.Conclusion The meta-analysis suggests that ACE I/D polymorphism is associated with increased risk of RPL. The ACE I/D polymorphism may be a risk factor for RPL in Caucasian and West-Asian populations, but not in East-Asians.
Keywords: miscarriage; pregnancy loss; angiotensin-converting enzyme; polymorphism; meta-analysis